KINSHIP AND COMMUNITY IN THE NORTHERN SOUTHWEST: CHACO AND BEYOND. Issue 4 (October 2018) - Ware, John
Abstract : Archaeogenomic studies of a burial crypt in Pueblo Bonito, Chaco Canyon, New Mexico, have demonstrated the presence of an elite matrilineal descent group that spanned most of the 300+ years the great house was occupied, confirming, among other things, the deep antiquity of matrilineal ideologies among the Ancestral Pueblos of the northern Southwest. This article explores the sociopolitical implications of matrilineal descent, matrilocal residence, and Iroquois-Crow alliance structures among the Ancestral Pueblos of Chaco and elsewhere. It argues that matrilineal ideologies helped shape community forms and intercommunity relations throughout the Pueblo Southwest. It argues further that kinship provides insights into Chaco's eleventh-century expansion that dispersed "outlier" great houses over much of the southeastern Colorado Plateau. The article concludes with a call for archaeologists and cultural historians to pay more attention to kinship, the principal idiom of social, economic, and political relations in nonstate societies. Abstract : Estudios arqueogenómicos de una cripta funeraria en Pueblo Bonito, Chaco Canyon, Nuevo México, han demostrado la presencia de un grupo de descendencia matrilineal de élite que abarcó la mayor parte de los más de 300 años durante los cuales estuvo ocupada la gran casa, confirmando, entre otras cosas, la profunda antigüedad de las ideologías matrilineales entre los Pueblos Ancestrales del Sudoeste septentrional. Este artículo explora las implicaciones sociopolíticas de la descendencia matrilineal, la residencia matrilocal y las estructuras de alianza Iroquois-Crow entre los Pueblos Ancestrales del Chaco y otros lugares. Se sostiene que las ideologías matrilineales ayudaron a plasmar las formas comunitarias y las relaciones intercomunitarias a lo largo de la región Pueblo del Suroeste. Se sostiene además que el parentesco proporciona información sobre la expansión de la sociedad Chaco en el siglo once que dispersó grandes casas "periféricas" en gran parte del sudeste de la meseta del Colorado. El artículo concluye con un llamado para arqueólogos e historiadores culturales a prestar más atención al parentesco, la expresión principal de las relaciones sociales, económicas y políticas en las sociedades no estatales.